2013
DOI: 10.1002/anie.201305734
|View full text |Cite
|
Sign up to set email alerts
|

A Fluorescent Probe for Investigating the Activation of Anticancer Platinum(IV) Prodrugs Based on the Cisplatin Scaffold

Abstract: Watching closely: A fluorescent probe was engineered to detect the clinically relevant platinum drug cisplatin within a complex cellular environment, thus providing a direct means for visualizing its cell entry and the activation of platinum(IV) prodrugs in cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 47 publications
0
33
0
Order By: Relevance
“…While no direct correlation between the reduction potential and prodrug efficacy has been established in the literature, a reduction potential in the mid-range as observed for complexes with two axial carboxylate ligands (~− 600 mV) seems to be a good guideline for an effective Pt(IV) prodrug [1]. The reduction of Pt(IV) complexes has been investigated in the past with different techniques and under different conditions [47][48][49][50][51]. It is generally presumed that under physiological conditions Pt(IV) is reduced by low-molecular-weight reducing agents such as ascorbic acid or glutathione, although recently evidence has been obtained that higher molecular weight biomolecules such as metallothioneines can also play a major role in the reduction and activation of Pt(IV) prodrugs [52].…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…While no direct correlation between the reduction potential and prodrug efficacy has been established in the literature, a reduction potential in the mid-range as observed for complexes with two axial carboxylate ligands (~− 600 mV) seems to be a good guideline for an effective Pt(IV) prodrug [1]. The reduction of Pt(IV) complexes has been investigated in the past with different techniques and under different conditions [47][48][49][50][51]. It is generally presumed that under physiological conditions Pt(IV) is reduced by low-molecular-weight reducing agents such as ascorbic acid or glutathione, although recently evidence has been obtained that higher molecular weight biomolecules such as metallothioneines can also play a major role in the reduction and activation of Pt(IV) prodrugs [52].…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…12 The intracellular reduction has been demonstrated by XANES spectroscopy and fluorescence techniques. [13][14][15] It has been reported that the physicochemical properties of Pt(IV) complexes, such as aqueous solubility or lipophilicity, can be tuned by modification of the axial substituents. 16 Tranilast is commercialized as an antiallergy drug used for the treatment of inflammatory diseases.…”
mentioning
confidence: 99%
“…It is thus consistent with the model studies using 3 and 5′-GMP noted above and is in line with recently published studies of Pt(IV) complexes. [15] Nevertheless, even under conditions of photoirradiation with laboratory light, conjugate 4 is much less reactive towards DNA than cisplatin. This finding is thought to reflect the slow light-induced reduction kinetics operative in the case of species such as 3 and 4 and the corresponding release of only a few active platinum(II) complexes at a time.…”
Section: Resultsmentioning
confidence: 99%